The Role and Regulation of the 11 Beta-Hydroxysteroid Dehydrogenase Enzyme System in Patients with Inflammatory Bowel Disease - Hussey, M.; Holleran, G.; Smith, S.; Sherlock, Mark; McNamara, D. (Digestive diseases and sciences, 2017)
Introduction Glucocorticoids are known to modulate a number of immunological responses including counteracting inflammation. Within tissues expressing the glucocorticoid and mineralocorticoid receptors including the colon, glucocorticoid metabolism is regulated by the isoenzymes of 11ß-hydroxysteroid dehydrogenase (11β-HSD). 11β-HSD1 acts as an oxidoreductase converting inactive cortisone into active cortisol, while 11β-HSD2 acts as a dehydrogenase converting active cortisol to inactive cortisone. Hexose-6 phosphate dehydrogenase (H6PDH) is a key regulator of 11β-HSD1 activity via its generation of NADPH. Variations in the 11β-HSD enzyme system in relation to levels of expression and regulation may have a role in IBD. The aim of this study was to investigate possible abnormalities of 11β-HSD enzyme system in the colon of patients with IBD. Methods By using quantitative real-time PCR, we investigated the transcription levels of 11β-HSD1 and 2 in colonic tissue from IBD patients and healthy controls undergoing a colonoscopy for disease assessment. Disease activity was recorded using clinical (Mayo Score/Harvey–Bradshaw Index), Biochemical (C-reactive protein), histological, and endoscopic parameters. In addition, transcription levels of H6PDH and the glucocorticoid receptor alpha (GR-α) as well as key pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, Rela (subunit for NF Kappa B)) were later examined among this group, and results were correlated with 11β-HSD2 gene expression. Results and patient demographics were expressed as a mean (and SD), and differences between IBD patients and control groups were analyzed using a Student’s t test or Mann–Whitney U test as appropriate, with a p value of ≤0.05 considered significant. Results were controlled for disease activity as outlined above. Results Results have demonstrated a significant downregulation in 11β-HSD2 expression in IBD patients compared with controls (13.8 ± 17.1 au vs. 318.4 ± 521.1 au, p = 0.01), whereas levels of 11β-HSD1 did not appear to vary across the two groups. Among IBD patients, there was a trend toward higher 11β-HSD1 expression in inflamed tissue compared with matched non-inflamed tissue (422.1 ± 944 au vs. 102.2 ± 103.9, P = 0.09). Levels of H6PDH and the GR-α expression did not appear to vary among active inflamed IBD tissue and controls. As a result, we examined the association between pro-inflammatory cytokines and levels of 11β-HSD2 expression. Results showed an upregulation of key pro-inflammatory cytokine mRNA expression (TNF-α, IL-1β, IL-6) during inflammation with an associated downregulation of 11β-HSD2 mRNA expression when compared to controls. Dysregulation in this pathway could have a potential role in IBD pathogenesis and may account for exogenous glucocorticoid resistance in IBD. Further work assessing the role of the 11β-HSD enzyme system in steroid-resistant subjects is warranted.